Effects of Fish Oil (SMOFlipid®) and Olive Oil Lipid (ClinOleic®) on Neonatal Morbidities in Preterm Infants - Fatih KILICBAY; Aslı KESKIN; Ayla GUNLEMEZ (Medeniyet Medical Journal)
Objective: Total parenteral nutrition (TPN) is very important for providing optimal nutrition during the critical developmental period of preterm newborns. Thus, there is a need to optimize TPN solutions to reduce morbidities. This study aimed to examine the effects of olive oil (ClinOleic®) and fish oil (SMOFlipid®) therapies on the frequencies of neonatal morbidities. Methods: Premature newborns hospitalized in the neonatal intensive care unit and receiving TPN for at least 14 days were included in the study. Newborns who were hospitalized and received olive oil-based lipid (ClinOleic®) were included in the olive oil group, and those who received omega-3 containing multi-lipid (SMOFlipid®) were included in the SMOFlipid group. Results: This study enrolled a total of 222 very-low-birth-weight premature newborns. The breastfeeding rate in the olive oil group was significantly lower than that in the SMOFlipid group (p<0.05). The rate of necrotizing entercolitis (NEC) in the olive oil group was significantly higher than that in the SMOFlipid group (p<0.05). The rate of bronchopulmonary dysplasia (BPD) in the SMOFlipid group was lower than that in the olive oil group (p<0.05). Conclusions: The rates of BPD and NEC were lower in the fish oil group. In this situation, fish oil therapy may provide protection against the development of BPD and NEC. Prospective studies are needed to determine whether this is caused by lipid therapy or an effect of breast milk.